Trends and challenges in chemoinformatics research in Latin America - Miranda Salas, Jazmín (2023)
Chemoinformatics is an independent inter-discipline with a broad impact in drug design and discovery, medicinal chemistry, biochemistry, analytical and organic chemistry, natural products, and several other areas in chemistry. Through collaborations, scientific exchanges, and participation in international research networks, Latin American scientists have contributed to the development of this subject. The aim of this perspective is to discuss the status and progress of the chemoinformatic discipline in Latin America. We team up to provide an author´s perspective on the topics that have been investigated and published over the past twelve years, collaborations between Latin America researchers and others worldwide, contributions to open-access chemoinformatic tools such as web servers, and educational-related resources and events, such as scientific conferences. We conclude that linking and fostering collaboration within each nation as well as among other Latin American nations and globally is made possible by open science and the democratization of science. We also outline strategic actions that can boost the development and practice of chemoinformatic in the region and enhance the interaction between Latin American countries and the rest of the world.